The Implementation of IjtihÄd JamÄ'iy in MUI's Fatwa Commission - Bahrudin, Moh.; Suryanto, Tulus; Aslam, Mohd Mizan bin Mohammad (LP2M - Universitas Islam Negeri (UIN) Walisongo, 2020)
The Holy Quran and Sunnah contain universal values that require correct reasoning to be understood and applied by the Muslims. In this context, the scholars have been justified by Allah Almighty to undertake the ijtihÄd and ijmÄâ€™. This study aims to describe the ijtihÄd jamÄâ€™iy (collective ijtihÄd theory), as well as to analyze the impleÂmentation of ijtihÄd jamÄâ€™iy at MUIâ€™s Fatwa Commission in Lampung. This study is a combination of literature and field research. The data were obtained through literature studies of books, articles, and journals in related issues. Besides, the authors also interviewed MUI members to gain deeper information. Theoretically, the contemporary ijmÄâ€™ process can be pursued by an independent forum to conduct studies until a consensus is obtained from the majority of the participants. The panel must involve all religious elements in a representative manner. The practice of establishing Islamic law carried out by MUIâ€™s Fatwa Commission of Lampung Province is in accordance with the concept of ijtihÄd jamÄâ€™iy in the science of uá¹£Å«l fiqh. This analysis is important so that people have a high level of compliance after knowing that the MUI Lampung fatwa is ijma, which in fact is one of the sources of Islamic law.